Creative industry clusters, regional innovation and economic growth in China1. Issue 4 (November 2014) - Yu, Wentao; Hong, Jin; Zhu, Yunhao; Marinova, Dora; Guo, Xiumei; Kourtit, Karima; Wen, Yuyuan; Nijkamp, Peter
Abstract This paper explores the impacts of creative industries cluster (CIC) on regional innovation and economic growth in China. Regional innovation (i.e., upstream) is measured by regional novelty‐centred patent and efficiency‐centred patent, while regional growth (i.e., downstream) is measured by value added growth both in traditional industries and high technology industries. Then we establish models to estimate these two effects, using China's provincial panel data from 2003 to 2009. The results suggest both the upstream and downstream effects are significantly supported in statistics. We hence argue that it should be implemented to retain and establish more CIC zones in China.